Bridging smallholder farmers to climate information: the role of agricultural advisors in KwaZulu-Natal, South Africa - Ncoyini-Manciya, Zoleka; Manciya, Sixolise (Frontiers in Climate, 2026)
Food insecurity remains a persistent challenge in many African countries, where smallholder farmers depend heavily on climate-sensitive agricultural systems. Agricultural Advisors (AAs) are positioned to support farmers’ adaptation efforts, yet their capacity to access, interpret, and disseminate climate information remains insufficiently understood. This study examined AAs access to climate information, whether they disseminate it to farmers, and whether the information aligns with farmers’ practical decision-making needs. A mixed-methods approach was employed, combining semi-structured questionnaires administered to 77 AAs in the Ugu and Harry Gwala districts of KwaZulu-Natal, South Africa, with six focus group discussions involving smallholder farmers. Quantitative data were analysed using SPSS v28 and Excel, while qualitative data employed thematic analysis through Nvivo14. Results indicate that most of the AAs access seasonal climate forecasts, early warning data, and long-term climate projections. However, only 7.8% received the information from the South African Weather Service (SAWS). While 78.5% reported creating awareness on climate change and 72.5% on adaptation measures, only 32.4% felt confident advising farmers on coping strategies. Only 27.2% reported receiving sufficient information, 40.6% reported limited understanding of available adaptation strategies, and 45.3% had not initiated adaptation measures in their areas. Farmers similarly reported minimal engagement with AAs on climate guidance. These findings reveal a disconnect between climate information access and the delivery of practical, actionable advice. By examining both the AAs and farmers’ sides, the study provides locally grounded insights into extension service effectiveness. Targeted capacity-building for AAs and strengthened advisor–farmer interactions are essential to improve confidence, access to reliable, site-specific information, and provision of actionable guidance, supporting practical adaptation, enhancing smallholder resilience, thereby contributing to SDGs 1, 2, and 13.